LITERATURE REVIEW COMPETENCY AND PERFORMANCE IMPROVEMENT: TRAINING AND LEARNING ORGANIZATION ANALYSIS - Dedi Sutomo (Dinasti Publisher, 2022)
Previous research or research or relevant research is fundamental in research or scientific article. The existence of previous research or relevant research serves to strengthen the theory and phenomena of the relationship or influence between variables. This article reviews the Determination of Competency And Performance Improvement: Training And Learning Organization Analysis, a Human Resource Management Literature study. This article aims is to build a hypothesis of the influence between variables to be used in further research. The results of this research library are, that: 1) Training affects Competency Improvement; 2) Learning Organization affects Competency Improvement; 3) Training affects Employee Performance; 4) Learning Organization affects Employee Performance; and 5) Competency Improvement affects Employee Performance.